In vivo antiaging effects of alkaline water supplementation - Mariantonia Logozzi; Davide Mizzoni; Rossella Di Raimo; Mauro Andreotti; Daniele Macchia; Massimo Spada; Stefano Fais (Taylor & Francis Group, 2020)
Telomeres length and telomerase activity are currently considered aging molecular stigmata. Water is a major requirement for our body and water should be alkaline. Recent reports have shown that aging is related to a reduced water intake. We wanted to investigate the effect of the daily intake of alkaline water on the molecular hallmark of aging and the anti-oxidant response. We watered a mouse model of aging with or without alkaline supplementation. After 10 months, we obtained the blood, the bone marrow and the ovaries from both groups. In the blood, we measured the levels of ROS, SOD-1, GSH, and the telomerase activity and analysed the bone marrow and the ovaries for the telomeres length. We found reduced ROS levels and increased SOD-1, GSH, telomerase activity and telomeres length in alkaline supplemented mice. We show here that watering by using alkaline water supplementation highly improves aging at the molecular level.